Relationship between The Use of Personal Protection Equipment (PPE) with Farmers' Complaints due to Pesticides (Case Study in Subak Sri Gumana, Rejasa Village, Tabanan Regency) - Suwimantra , I Made Galih; Sucipta , I Nyoman; Tika , I Wayan (Jurnal BETA (Biosistem dan Teknik Pertanian), 2022)
The usage of pesticides that do not by following the rules can give a negative impact on human health and the environment. This study aims to determine a relationship between usage of Personal Protective Equipment (PPE) with farmer complaints due to pesticides in Subak Sri Gumana, Rejasa Village, Tabanan Regency. This study used samples amount 30 people (16%) from 189 farmers in Subak Sri Gumana. The instrument used the questionnaire Likert scale which provides choices for respondents to answer. Based on the result of chi-square test, the p-value is 0.002 (p <0.05), so there was a relationship between usage of Personal Protective Equipment (PPE) with farmer complaints due to pesticides in Subak Sri Gumana, Rejasa Village, Tabanan Regency. The conclusion is found a relationship between the usage of personal protective equipment (PPE) with farmers complaints due to pesticides in Subak Sri Gumana, Rejasa Village, Tabanan Regency. These complaints arise because farmers haven’t used Personal Protective Equipment (PPE) and ignore the dangers of using pesticides.